GAMBARAN PENGETAHUAN MAHASISWA FAKULTAS KEDOKTERAN PROGRAM STUDI PENDIDIKAN DOKTER UNIVERSITAS LAMPUNG ANGKATAN 2021 TERHADAP ANESTESI DAN PERAN DOKTER SPESIALIS ANESTESI - Javinka Fairuz Zahrani; Liana Sidharti; Nurul Islamy; Bambang Eko Subakti (Medula, 2023)
Anesthesia is an action in the medical field that is carried out intentionally on healthy patients and patients who have a disease from mild to severe with the aim that the patient does not feel sick when surgery is performed. This study aims to describe the knowledge of students of the Faculty of Medicine, Medical Education Study Program, University of Lampung on anesthesia and the role of anesthesiologists. This study used a descriptive cross-sectional research method on 136 samples selected through simple random sampling technique. The study used a questionnaire given via google form. The data were analyzed univariately to describe the knowledge of students of the medical faculty of the Lampung University medical education study program on anesthesia and the role of anesthesiologists. The results showed that 12 respondents (8.8%) had good knowledge, 54 respondents (39.7%) had sufficient knowledge, and 70 respondents (51.5%) had less knowledge about anesthesia and the role of anesthesiologists. . The conclusion in this study was that students of the medical faculty of the Lampung University medical education study program class of 2021 still lacked knowledge about anesthesia and the role of anesthesiologists.